Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.14309/ctg.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Yield of Wide-Area Transepithelial Sampling for Dysplasia Detection After Advanced Imaging and Random Biopsies in Barrett's Esophagus

Abstract: INTRODUCTION: Little is known about the additive yield of wide-area transepithelial sampling with computer-assisted three-dimensional analysis (WATS-3D) after a thorough examination with advanced imaging. The aim was to evaluate the adjunctive yield of WATS-3D after advanced imaging. METHODS: This is an observational cohort study from January 2017 to December 2018 for consecutive patients who underwent an examination that consists of high-definition whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Rigorous examination or oversampling of certain hot zones for dysplasia may help overcome this. In addition, relatively new to BE surveillance is the wide area transepithelial (WATS) brush ( 22 , 23 ). This brush has been shown to increase dysplasia yield versus pinch biopsies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous examination or oversampling of certain hot zones for dysplasia may help overcome this. In addition, relatively new to BE surveillance is the wide area transepithelial (WATS) brush ( 22 , 23 ). This brush has been shown to increase dysplasia yield versus pinch biopsies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 29 cases detected by WATS 3D , 23 cases were negative with FB but only 1 case detected by FB was missed by WATS 3D [ 12 ]. Finally, an observational cohort study that spanned 2 years and included 138 patients showed an added yield of 34.3% when WATS 3D was used in conjunction with FB [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is fast and efficient, and has been shown to have a better diagnostic yield compared to FB following the Seattle protocol [ 20 ]. However, a recent study showed that WATS 3D further increased the diagnostic yield when added to white light endoscopy, NBI, VLE and FB following the Seattle protocol [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective cohort, retrospective cohort, or case-control studies of endoscopic screening to forecast the mortality and incidence of early gastric cancer will be included to pool and review in this study. Studies assessing the effect of endoscopic screening only in individuals with premalignant conditions, [ 13 ] Barrett esophagus, [ 14 ] and Helicobacter pylori [ 15 ] ( H pylori ) infection were excluded.…”
Section: Methodsmentioning
confidence: 99%